Genetic Diversity of Unhatched Sea Turtle Eggs in Buleleng, Bali Indonesia Hatchery Based on The Mitochondrial Control region Locus - Immanuel Pratama; Ni Putu Dian Pertiwi; I Made Oka Riawan; Ni Luh Astria Yusmalinda; Luh Putu Candra Apriliani; Ni Komang Rossa Sri Savitri; Srie Marhaeni Julyasih, Ketut; Jafron Syah, Moh; Rita Rachmawati; Andrianus Sembiring (Universitas Airlangga, 2025)
Sea turtles are protected animals that are threatened with extinction due to natural and anthropogenic factors such as coastal erosion and illegal trade. This study aims to analyze the genetic diversity of sea turtles in Buleleng using mitochondrial DNA from unhatched egg samples. Samples were collected from two nests at several breeding sites to determine genetic variation within a single conservation area. Molecular analysis was conducted on the control region locus with a sequence length of 869 bp. The results of the identification showed that the samples originated from three species: green sea turtles (Chelonia mydas), olive ridley sea turtles (Lepidochelys olivacea), and hawksbill sea turtles (Eretmochelys imbricata), with sequence similarities of 99.44%–99.77%. The phylogenetic tree formed four clades with bootstrap values of 79–100%, supporting the classification and kinship relationships between species. Low intraspecific genetic distance (0–0.2%) and interspecific genetic distance (16.4–21.4%) indicate high similarity within a species and significant differences between species. The results of this study can be used to strengthen effective genetics-based sea turtle conservation programs in the Buleleng region of North Bali.